Mechanical Properties of 3D Printed Reinforced Polycaprolactone Composite Scaffolds - Amdjadi, Parisa; Khoshroo, Kimia; Seifi, Massoud; Tahriri, Mohammadreza; Tayebi, Lobat (Journal of Dental School, 2021)
Objectives This paper describes the fabrication of a new porous 3D-printed scaffold composed of polycaprolactone (PCL) and polyether-ether ketone (PEEK) micro-particles for bone tissue engineering (BTE) applications. Methods In order to improve the compatibility of the reinforcing PEEK powder with polycaprolactone, the PEEK powder was surface-modified by an amino-silane coupling agent. After modification, Fourier-transform infrared spectrometry (FTIR) and differential scanning calorimetry (DSC) were used to investigate the chemical reaction between PEEK and silane coupling agent. In order to increase the compressive modulus of the 3D printed PCL scaffold, 10% silane-modified PEEK was incorporated into the PCL polymeric matrix. Scanning electron microscopy (SEM) was used for cell morphology and attachment evaluation. Results The results indicated that the silane coupling agent was successfully grafted onto the particle surface. The compressive modulus of PCL scaffold increased by incorporating the silane-modified PEEK, despite having higher porosity, compared with the pure PCL scaffolds. Addition of amino-silane had a positive impact on cell response, and that surface modification led to improved particle dispersion. Conclusion In conclusion, it seems that the incorporation of surface-modified PEEK micro-particles into the PCL porous scaffold could enhance its mechanical properties, and may be applicable for the management of large bone defects.